Strategy for Developing the Potential of Batu Lawang Tourism Through the Digital World in Cupang Village, Gempol District, Cirebon Regency - Syifa Paujiyah; Muhammad Ikhsan Ghofur (Prosperity: Journal of Society and Empowerment, 2022)
Cupang Village is one the villages located in Gempol District, Cirebon Regency, which is the southernmost tip. Cupang Village has an area of +/- 192,000 Ha. With a population of around 3,828 people or 1,226 households and a population density od 199 per/km. Cupang Village is a village thas has a lot of potential to be developed. One of them is the potential of a tourist village owned by Cupang Village in the form of natural tourism called Batu Lawang. However, currently the potential in the Batu Lawang tourism sector has not been widely exposed to the public. This study aims to determine the strategy in introducing Batu Lawang Tourism through the digital world to the wider community. This study uses qualitative methods with research techniques of observation, interviews, Focus Group Discussion, participation, asset based community development and documentation. The result of this study are the development strategy of Batu lawang tourism by conducing Focus Group Discussion to related pasties, making banners, making accessories that function to beautify documentation and making promotional videos for Batu Lawang tourism.